Correction: Dengue seroprevalence and force of primary infection in a representative population of urban dwelling Indonesian children. - Ari Prayitno; Anne-Frieda Taurel; Joshua Nealon; Hindra Irawan Satari; Mulya Rahma Karyanti; Rini Sekartini; Soedjatmiko Soedjatmiko; Hartono Gunardi; Bernie Endyarni Medise; R Tedjo Sasmono; James Mark Simmerman; Alain Bouckenooghe; et al. (Public Library of Science (PLoS), 2018)
[This corrects the article DOI: 10.1371/journal.pntd.0005621.].